Genetic relationships of Kampung, Pelung, Sentul and Black Kedu Chicken using Microsatellite DNA Markers: I. Lingkage group of macro chromosome - Sartika, Tike; Iskandar, S; Prasetyo, L.H; Takahashi, H; Mitsuru, M (Indonesian Journal of Animal and Veterinary Sciences, 2004)
Genetic relationships of Kampung, Pelung, Sentul and Black Kedu chickens were studied on the basis of microsatellite DNA polymorphism. DNA samples were analyzed using nine microsatellite markers which chosen from linkage group of macrochromosome (chromosome 1-8) such as, locus ABR 258, ABR359, ABR 297, ABR 339, ABR 75, ABR 209, ABR 28, ABR 419 and ABR 604. Analyses of amplified DNA fragments were performed using Gene Mapper 2.0 software (PE, Applied Biosystems). The allele frequencies in each breed estimated by direct counting. Since all nine microsatellite markers were polymorphic, genetic distance between the breeds could be calculated based on the frequencies of alleles of the microsatellite. Genetic relationships between the breeds could be constructed. The results indicated that a total of 73 allele were detected while typing all the four breeds of local chicken and one breed of White Leghorn as outgroup breed acrossed nine loci. The number of alleles was observed in all of the breed ranged 3-17 alleles according to the microsatellite under scrutiny. Highest observed number of alleles was found in Kampung Chicken 60 alleles (82.2%). The UPGMA method for dendogram based on Nei genetic distances indicated that the local chickens have the same of ancestor, while Kampung and Sentul chicken have the same cluster followed by Black Kedu and Pelung Chicken. Â  Key words: Local chicken, microsatellite, macrochromosome, genetic distance